RANCANG BANGUN ALAT DEMONSTRASI TESLA COIL DALAM PEMBELAJARAN MEDAN MAGNET - Sindim, Excelcis Deo Christianto; Makahinda, Tineke; Rampengan, Alfrie Musa; Lahope, Kenny Setiawan (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to design a feasible, effective and practical magnetic field demonstration tool used in physics learning at school. This demonstration tool is a Tesla Coil which is a coil that oscillates and produces a magnetic field. The method used is development research (R & D) 4D model. This research was conducted in October 2024 at Karitas Tomohon Catholic High School for 25 students. The results of the study were seen from three aspects, namely feasibility, effectiveness and practicality. The feasibility results were obtained through the assessment of a team of material experts and media experts. The final result of the media expert team assessment was 93.75% and the material expert team assessment was 91.66%. Effectiveness data is obtained from student learning outcomes data through pre-test and post-test instruments. Through the T-test analysis, there is a significant difference between the learning outcomes of control class students and experimental classes. Practicality data is obtained through a questionnaire filled out by students. Practicality analysis shows a value of 85.23% in the strongly agree category and 14.76% in the agree category. Teacher response to the product scored 93%.T hus it can be concluded that the Tesla Coil Demonstration Tool is declared feasible, effective and practical to use in learning activities.